Inferior vena cava thrombosis as a cause of haemolysis in a patient on ECMO. (March 2017) - Wills, Samantha; Forrest, Paul
Haemolysis, thrombosis and haemorrhage are well-documented complications of extracorporeal membrane oxygenation. This case report outlines an unusual case of haemolysis, thought secondary to a large mobile thrombus in the inferior vena cava.